2021
DOI: 10.3390/molecules26092403
|View full text |Cite
|
Sign up to set email alerts
|

How Different Snacks Produce a Distinct Effect in Salivary Protein Composition

Abstract: Saliva secretion changes in response to different stimulation. Studies performed in animals and humans suggest that dietary constituents may influence saliva composition, although the dynamics of these changes, and how they are specific for each type of food, are little known. The objective of the present study was to access the short-term effects of different foods in salivation and salivary protein composition. Twelve participants were tested for four snacks (yoghurt, bread, apple and walnuts). Non-stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
3
2
0
Order By: Relevance
“…The short-term plasticity of saliva in response to food or food stimuli is not a surprise, since it was previously observed in studies from our lab [ 33 , 46 ] and from other authors [ 47 ]. Looking for SDS-PAGE profiles, our participants increased the relative levels of the bands expected to contain albumin, α-amylase, PRPs, and cystatins, which, with the exception of albumin, are all salivary proteins observed to bind and precipitate apple polyphenols, as discussed above.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The short-term plasticity of saliva in response to food or food stimuli is not a surprise, since it was previously observed in studies from our lab [ 33 , 46 ] and from other authors [ 47 ]. Looking for SDS-PAGE profiles, our participants increased the relative levels of the bands expected to contain albumin, α-amylase, PRPs, and cystatins, which, with the exception of albumin, are all salivary proteins observed to bind and precipitate apple polyphenols, as discussed above.…”
Section: Discussionsupporting
confidence: 66%
“…The effect of food intake in the saliva proteome has been reported in different studies [ 13 , 33 ]. Tannins are probably the compounds present in vegetable foods more associated with direct effects at the salivary protein level, since these polyphenolic compounds have a particular affinity for some types of salivary proteins, binding them.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study found 70 different peaks on CM10 chips (39 in the range of 2-10 kDa, 17 from 10-20 kDa, and 14 from 20-100 kDa) and a total of 108 peaks on the Q10 chips with most peaks in the range of below 10 kDa [43]. These findings are in line with the results of the present investigation, while other studies reported from total numbers that ranged between 70 and >1000 proteins [14,[44][45][46].…”
Section: Discussionsupporting
confidence: 92%
“…When it comes to food, the complexity of the issues involved has to be acknowledged, because food is much more than a sum of nutrients, and food choices involve from primary senses to memories, beliefs, and more [13][14][15][16][17][18], as is the case of the MD.…”
Section: A Broken Global Food System What Way Out?mentioning
confidence: 99%